JENIS DAN POLA KALIMAT MAJEMUK PADA WACANA NONSASTRA DALAM BUKU TEKS BAHASA INDONESIA KELAS XI SMA SERTA IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Rini Setyowati; Wini Tarmini; Imam Syafi’i (Prosiding Seminar Nasional Berseri, 2020)
This study aims to describe the types and patterns of compound sentences in non-literary discourse in the Indonesian Language Class XI SMA Textbooks and their implications for Indonesian language learning. The method used in this study is descriptive qualitative with content analysis techniques. The object of this research is non-literary discourse in the form of explanatory text with a focus of research in the form of compound sentences on non-literary discourse in Indonesian Text Books Class XI SMA. The instrument used in this study is an instrument from the researcher himself, namely in the form of data analysis tables. The results of this study indicate that, 1) Compound sentence types in non-literary discourse Class XI Indonesian textbooks are 3 types, namely equivalent, multilevel, and mixed, 2) Compound sentence patterns are equivalent to only one type, compound sentences equivalent to sum, while multilevel compound sentences there are four types, namely independent-dependent order, dependent-independent, relative clauses, and non-conjunction sentences.